Narcissism, beliefs about controlling interpersonal style, and moral disengagement in sport coaches. Issue 5 (2nd September 2020) - Matosic, Doris; Ntoumanis, Nikos; Boardley, Ian D.; Sedikides, Constantine
Abstract : We tested the relations among narcissism (including both its adaptive and maladaptive facets), effectiveness and normalcy beliefs about controlling interpersonal style, controlling coach behaviours, and moral disengagement in sport coaches. Participants were 210 sport coaches, representing a variety of sports and levels of coaching. Coaches completed a multi-section questionnaire assessing the study variables. Path analyses revealed that global narcissism and maladaptive narcissism were positively associated with controlling coach behaviours. Furthermore, effectiveness and normalcy beliefs about controlling interpersonal style were positively associated with controlling coach behaviours, while controlling coach behaviours were positively associated with coach moral disengagement. Finally, adaptive narcissism had an indirect effect on controlling coach behaviours via effectiveness beliefs about a controlling interpersonal style. These findings contribute to the literature on antecedents and outcomes of controlling coach behaviours, as reported by coaches.